Analyzing the Effect of Geothermal Steam Quality Employing Performance of Single Cylinder Double Flow Turbine - Elli Prastyo; Ninin Asminah; Yully Mulyani; Indah Dhamayanthie; Muhammad Tarish (International Journal of Integrated Engineering, 2025)
The quality of steam in geothermal power plants is of critical importance, as it directly affects the thermodynamic properties of enthalpy and entropy. Consequently, it plays a decisive role in determining the reliability and performance of the turbine system. Operating data obtained from the Quality Control Unit and Central Control Room between 1 and 30 June 2024 were analyzed to determine enthalpy and entropy values through linear interpolation using the SteamTab Companion software. This study aims to evaluate turbine efficiency and gross power output as functions of steam quality, enthalpy, non-condensable gas (NCG) content, and silicon dioxide (SiO?) concentration over a 30-day observation period. The analysis revealed that the highest steam quality (0.8065) corresponded to an isentropic efficiency of 81.83% on day 11. The maximum actual enthalpy of 2506.040 kJ/kg produced a gross power output of 56,130.493 kW. Conversely, the lowest steam quality (0.80281) resulted in an isentropic efficiency of 79.13% and an actual enthalpy of 2496.99 kJ/kg, with a gross power output of 54,823.975 kW on day 3. The geothermal steam contained an average NCG content of 1.34% and an average SiO? concentration of 85.2 ppm. These concentrations were found to significantly influence turbine performance, as reflected by the variations in isentropic efficiency and gross power generation. The findings of this study indicate a direct proportional relationship between steam quality and the turbine’s isentropic efficiency, enthalpy, and gross power output.